The Effect of the Rule of Benevolence on the Doctor's Responsibility; Comparative Case Study: Iranian and American Law - Fatemeh Alizadeh; Ardavan Arzhang; Rasoul Rafiee (پژوهشهای حقوقی)
The civil responsibility of the doctor in Iranian and American law is based on the theory of fault. With the difference that according to Article 495 of the Islamic Civil Code, the fault of the doctor is assumed and he must prove his innocence. According to the Good Samaritan Laws, to remove the civil and criminal liability from the doctor, the mere act of good faith is sufficient, provided that he has not committed a gross fault, even if there are emergency conditions in the hospital environment or outside of that environment. According to Iran's laws - based on Article 509 of the Islamic Civil Code - including the implementation of the rule of beneficence towards the doctor and the loss of the guarantee from him, in addition to having good intentions, this means that he should not commit fault and aggression in practice. The mere act of good faith only causes his criminal liability (and not civil liability) to be removed. The prohibition of beneficence in citing harm to the benevolent doctor and the conventional proportionality between benevolent action and avoided harm are among the elements of benevolence.